Effects of Total Aromatic Hydrocarbons in Water and Sediment of Shatt Al- Arab River on the Biochemical components of Mud Crab Chiromentes boulengeri (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study was conducted to evaluate the effects of Total Aromatic Hydrocarbons (TAH) on the biochemical components of  haemolymph of mud crab Chiromentes boulengeri ( Calmen, 1920) that distributed along the bank of Shatt Al-Arab River / Southern of Iraq. Seasonal samples of water sediment and crab were collected from tow stations Al-Salhiya in the south and Garmat Ali in the North , Samples were collected from February 2015 to January 2016. The environmental factors (Air Temperature , Water Temperature , pH , Salinity and Dissolved Oxygen) were measured, TAH in Water , Sediments and crab tissue  and the levels of biochemical components ( Glucose, Total Protein and Cholesterol) in haemolymph of crab were studded .The TAH concentrations in water were (38.88 – 23.36) µg/L, in sediment were (24.03 - 12.46) µg/g and in tissue were (26.48 - 14.17) µg/g in both stations respectively . Similarly , the average of TAH concentrations showed a significant seasonal variation in water , sediment and tissue samples in both stations at differences level of (P≤ 0.05) . The results of biochemical components showed that averages of the glucose were (24.5 – 31.85) mmol/L , while the averages of total protein ranged from (25.75 – 33.07) g/dL and the averages of cholesterol were (4.32 – 7.00) mmol/L. Total protein and cholesterol levels in the crab haemolymph differed significantly between the both stations (P≤ 0.05).